The moderating role of LMX in the relationship between work values and organizational identification: A cross-cultural study - Karahan, Merve; Bozkurt, Serdar (URAL STATE UNIV ECONOMICS, 2021)
Employee values have an important effect on the success of organizations since they shape people's behavior. Knowing the work values of employees benefits organizations and leads to positive organizational outcomes. This study aims to examine the relationship between work values and organizational identification, and to determine the moderating role of leader-member exchange within this relationship. The methodological framework of the study includes social exchange theory based on dyadic relationships, and also social identity theory underlining the question of Who am I? to attach with an organization. To rationalize the proposed model, the data was collected through an online survey from 288 employees in Turkey and Germany. Descriptive statistics, confirmatory factor analysis, and structural equation modeling were performed to test the model. According to the results, employees' work values are positively associated with organizational identification, and leader-member exchange moderates this relationship. The practical and theoretical implications of the study are to raise awareness about the ability of leaders for desired organizational outcomes due to the values employees have, and to contribute to the work values literature in terms of cross-cultural perspective.
Keywords: work values; organizational identification; leader-member exchange (LMX); cross-cultural study; Turkey; Germany; LEADER-MEMBER EXCHANGE; GENERATIONAL-DIFFERENCES; PERFORMANCE; MULTILEVEL; FRONTLINE; IDENTITY; BEHAVIOR; OUTCOMES; MODEL; Business & Economics